STRENGTHENING RELIGIOUS MODERATION IN ISLAMIC BOARDING SCHOOLS: COUNTERING RADICALIZATION THROUGH TOLERANCE- AND NATIONALITY-BASED EDUCATION - Rokimin,; Nanang Lidwan,; Sofwan Manaf,; Wawan Ridwan,; Ainur Alam Budi Utomo, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines the role of Islamic boarding schools (Islamic boarding schools) in promoting religious moderation in Indonesia, focusing on efforts to combat radicalization through education based on tolerance and nationalism. Islamic boarding schools have long been an integral part of shaping a moderate understanding of Islam, which is crucial in preventing radicalization and religion-based violence. However, despite significant efforts to develop religious moderation ideologies, the threat of radicalization remains present in some Islamic boarding schools. This research uses a literature review approach to analyze relevant academic sources related to the role of Islamic boarding schools in promoting the values ​​of religious moderation. The study highlights the importance of Islamic boarding school leaders, particularly Kiai, in promoting an inclusive and tolerant understanding of Islam, which can reduce the influence of extremism. The research also identifies challenges in the implementation of religious moderation, including cultural stigma, curriculum limitations, socio-economic barriers, and the increasing influence of social media in spreading extremist ideologies. The findings emphasize that Islamic boarding schools can serve as a broader model of Islamic education in Indonesia by integrating the values ​​of religious moderation into the curriculum and daily activities, prioritizing tolerance, justice, and peace. Furthermore, the study provides strategic recommendations to strengthen the role of Islamic boarding schools in fostering moderation, such as curriculum reforms, community involvement, and the use of digital platforms to spread moderate teachings. The results of this study are expected to contribute to the development of inclusive and moderate Islamic education, which can effectively address the challenges of radicalization and intolerance in Indonesia.